Judicial Stay of Administrative Decisions: A Comparative Analytical Study (Excerpt from a master’s thesis defended on July 19, 2017, at the Faculty of Law, University of Sulaymaniyah) - سعيد, دانا عبدالكريم; خەسرەو, پەریسا پەروێز (Sulaimani Journal for Humanities, 2020)
The judicial moratorium on the implementation of the administrative decision came as an exception to the general rule, "The non-stop effect of challenging the annulment of administrative decisions", and it was found to strike a balance between the public interest that the administration seeks to achieve through its activity, and the interest of individuals. In order for a decision to accept the endowment request by the judiciary, the request to suspend the implementation of the decision must be accompanied by a claim of annulment, and to be submitted during the appeal against the cancellation and in the same petition, or after it and with a separate request, and that the implementation of the decision would arrange irreversible results if he decides to cancel it , and to prove to the judge, upon his consideration of the request for a stay of execution, and through the apparent examination of the papers, that it is more likely that a ruling to cancel the decision subject to the stay request is canceled. Therefore, in studying the subject, comparative analytical approach has been adopted by dividing it into two main sections, the first for "the concept of the system of halting the implementation of the administrative decision", and the second for “the terms of accepting the request to suspend implementation”, and we concluded it with a set of conclusions and recommendations for the organization of the topic of the system of halting implementation of the administrative decision under Iraqi legislations and the Kurdistan region.